The Role of Global Health Partnerships in Infectious Disease Control: Lessons from Indonesia’s Response to Tuberculosis and COVID-19 - Astuti, Winda Dwi; Lumbantobing, Saula Bellatrix; Arvian, Shenia Rully; Anggraini, Mela Ratri; Naradhipa, Rasyid Araghani; Wasir, Riswandy (Universitas STRADA Indonesia, 2025)
Indonesia's dual burden of tuberculosis and COVID-19 has highlighted the critical role of global health partnerships in strengthening infectious disease control. This study examines how collaborations with organizations such as WHO, the Global Fund, and USAID have supported Indonesia's response, particularly in TB detection, case management, and pandemic adaptation. A qualitative literature review was conducted, analyzing ten peer-reviewed studies published between 2020 and 2025. The findings reveal that while global partnerships facilitated knowledge transfer, financial assistance, and digital innovation, challenges persist in coordination, private sector integration, and policy alignment. The study concludes that sustained commitment, institutional capacity, and harmonized governance are essential to maximize the impact of international cooperation on national disease control strategies.